Recovery and modification method for graphite negative electrode material of failed battery
By combining the recovered graphite negative electrode material with graphene oxide and silicon oxide and carbonizing at high temperature, a recycled graphite negative electrode material with silicon oxide-graphene is solved, and the problems of high energy consumption and environmental pollution in the existing technology are solved. , improves the capacity and circulation performance of materials, and achieves low-cost and environmentally friendly recycling.
Patent Information
- Application Number
- CN202411105684.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The existing graphite negative electrode material recycling technology has problems such as high energy consumption, high cost and environmental pollution, and the generation of toxic waste and purity are difficult to improve during the hydrometallurgy process.
By combining the recovered graphite negative electrode material with graphene oxide and silicon oxide, high-temperature carbonization treatment is carried out to form a recycled graphite negative electrode material of silicon oxide-graphite@graphene, improving its capacity and cycling performance, and ensuring graphite oxide through electrostatic adsorption The tight wrapping of enes inhibits the expansion of silicon oxide.
The low-energy consumption and low-cost graphite negative electrode material recovery and performance modification are achieved, the capacity, rate performance and cycle stability of the material are improved, and the impact of silicon oxide expansion is reduced.
Smart Images

Figure BDA0004990708410000091 
Figure BDA0004990708410000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a method for recovering and modifying graphite negative electrode materials of failed batteries. Background Art
[0002] At present, people are more concerned about the recycling of positive electrode materials when it comes to the recycling of waste lithium-ion batteries, while there is less research on the recycling of negative electrode materials of waste lithium-ion batteries. However, graphite is used in large quantities in lithium-ion batteries. Each kilowatt-hour of lithium-ion batteries requires about 1kg of graphite, and a small or medium-sized electric car requires about 50kg of graphite negative electrode materials. Therefore, the recycling and reuse of negative electrode graphite in waste lithium-ion batteries has important practical significance for reducing the production cost of battery-grade graphite, avoiding environmental pollution, and the sustainable development of the lithium-ion battery industry.
[0003] Existing graphite negative electrode material recycling technologies are mainly divided into pyrometallurgy and hydrometallurgy. Pyrometallurgy refers to heating the recycled graphite negative electrode material to above 3000°C, removing impurities to make the purity of graphite reach above 99.9%, and repairing the lattice defects generated after the graphite negative electrode material is charged and discharged. However, this method has high energy consumption and requires special equipment to purify the toxic gases produced by combustion, and the cost is relatively high. Hydrometallurgy refers to dissolving the metals in waste lithium batteries through acids, alkalis or other solutions, and then separating the graphite negative electrode material from the metal through deposition, extraction and other methods. Hydrometallurgy can save more energy consumption, reduce air pollution, and is relatively easy to operate. However, the acid and alkali solutions used in the recycling process will pollute the water body, and toxic wastes such as organic solvents will be produced in the hydrometallurgical process. In addition, if high-purity metals are to be produced in the hydrometallurgical process, the production cycle is relatively long. Summary of the invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a method for recycling and modifying graphite negative electrode materials of failed batteries. The method combines the recycling process with the performance modification of the recycled graphite, is simple to operate and has low energy consumption. By compounding the recycled graphite negative electrode material with graphene oxide and silicon oxide, not only the surface of the recycled graphite can be repaired, but also its capacity, rate performance and cycle performance can be greatly improved.
[0005] The present invention provides a method for recycling and modifying graphite negative electrode materials of spent batteries, comprising the following steps:
[0006] S1. Dispersing the negative electrode sheets of the failed battery in water, collecting the graphite negative electrode material separated from the current collector, washing with deionized water for multiple times, and filtering to obtain the recovered graphite negative electrode material;
[0007] S2, dispersing the recycled graphite negative electrode material, graphene oxide and silicon dioxide in a solvent respectively, mixing the obtained dispersions, and adding a reducing agent to carry out a reduction reaction to obtain a precursor composite material;
[0008] S3. Carbonizing the precursor composite material at high temperature to obtain a regenerated graphite negative electrode material.
[0009] In the present invention, a recycled graphite negative electrode material is used as a substrate, silicon dioxide (SiO) is doped, a layer of graphene oxide is coated on the surface by using a graphene oxide reaction, and then the graphene oxide is reduced by heating reaction with a reducing agent to convert the graphene oxide into reduced graphene oxide, thereby forming a regenerated graphite negative electrode material of silicon dioxide-graphite@graphene (G-SiO-rGO); on the one hand, the presence of SiO greatly improves the gram capacity of the negative electrode material, and on the other hand, the graphene coated on the outside has excellent mechanical properties, which can inhibit the expansion of SiO, and the graphene also repairs the surface of the recycled graphite negative electrode material; at the same time, the graphene has good electrical conductivity, which can improve the electrical conductivity of the negative electrode material and the charge and discharge speed of the battery, and the two-dimensional structure of the graphene enables the negative electrode material to have a high specific surface area, providing more active sites for the insertion and extraction of lithium ions, which can significantly improve the capacity and cycle stability of the battery.
[0010] Preferably, in step S1, the failed battery is a lithium-ion battery whose capacity has dropped to less than 80% of the initial capacity.
[0011] Preferably, in step S2, the graphene oxide is prepared by using a modified Hummers method; and the silicon oxide is nano silicon oxide.
[0012] Preferably, in step S2, the mass ratio of the recycled graphite negative electrode material, silicon oxide and graphene oxide is 10:0.5-1:0.2-0.5.
[0013] Preferably, in step S2, the solvent is at least one of water, ethanol, propanol, ethylene glycol or nitrogen methyl pyrrolidone;
[0014] Preferably, the solid content of the recycled graphite negative electrode material dispersed in the solvent is 5-15wt%, the solid content of the graphene oxide dispersed in the solvent is 0.1-1wt%, and the solid content of the silicon oxide dispersed in the solvent is 0.5-2wt%.
[0015] Preferably, in step S2, the silicon iodine is silicon iodine pretreated with quaternary ammonium;
[0016] Preferably, the quaternization pretreatment specifically comprises: performing a ring-opening coupling reaction on silicon oxide and epoxypropyltrimethylammonium chloride to obtain the product.
[0017] In the present invention, the silicon oxide pretreated by quaternary ammonium has positive charges due to the quaternary ammonium salt ions grafted on the surface, and the graphene oxide sheets have a large amount of negative charges due to the presence of abundant oxygen-containing functional groups. Therefore, after the silicon oxide pretreated by quaternary ammonium and the graphene oxide are compounded, the two can form electrostatic adsorption due to the different charges they carry, thereby ensuring the effective adsorption and wrapping of silicon oxide by graphene oxide, and finally forming a graphene layer with a tight bond and rich pore structure on the surface of silicon oxide, thereby further inhibiting the expansion of silicon oxide, and more effectively improving the rate performance and cycle performance of the regenerated graphite negative electrode material.
[0018] Preferably, the reducing agent is at least one of hydrogen, hydrazine hydrate or sodium borohydride.
[0019] Preferably, in step S3, the temperature of the high temperature carbonization reaction is 1000-1200°C and the time is 3-5h;
[0020] Preferably, the heating rate of the high temperature carbonization reaction is 5-10°C / min.
[0021] The present invention also provides a regenerated graphite negative electrode material obtained by the above-mentioned recovery and modification method.
[0022] The present invention also proposes an application of the above-mentioned regenerated graphite negative electrode material in a lithium ion battery.
[0023] The invention provides a method for recycling and modifying graphite negative electrode materials of failed batteries, which can effectively recycle graphite negative electrode materials, has a simple process, and is low in cost, and has practical application value for promoting the recycling and reuse of failed batteries. The invention simultaneously utilizes graphene oxide, silicon oxide and recycled graphite negative electrode materials for repair and capacity expansion, which improves the specific capacity while solving the problem of poor cycle stability of the obtained silicon oxide due to volume expansion during the charge and discharge process. DETAILED DESCRIPTION
[0024] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0025] The raw materials used in the following examples are all commercially available products, as follows:
[0026] Graphite powder: analytical grade, purchased from Shanghai Aladdin Reagent Co., Ltd.;
[0027] Sodium nitrate: analytical grade, purchased from Tianjin Damao Chemical Reagent Factory;
[0028] Concentrated sulfuric acid: analytical grade, Guangzhou Chemical Reagent Factory;
[0029] Potassium permanganate: analytical grade, purchased from Hengyang Kaixin Chemical Reagent Co., Ltd.;
[0030] Hydrogen peroxide: analytical grade, purchased from Tianjin Fuyu Fine Chemical Co., Ltd.;
[0031] Hydrochloric acid (HCl): analytical grade, purchased from Guangzhou Chemical Reagent Factory;
[0032] Nano-silicon dioxide (SiO) powder: analytical grade, purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0033] Hydrazine hydrate (N2H4·H2O): purchased from Sinopharm Chemical Reagent Co., Ltd.
[0034] Example 1
[0035] The present embodiment provides a method for recycling and modifying graphite negative electrode materials of spent batteries, which specifically includes:
[0036] (1) adding the negative electrode sheet of the lithium-ion battery after cycle failure to deionized water for ultrasonic dispersion, and after the graphite negative electrode material is completely separated from the current collector, taking out the current collector, collecting the obtained graphite negative electrode material, and then ultrasonically washing it with deionized water for 5 times, filtering it, vacuum drying it, and passing it through a 325-mesh sieve to obtain a recovered graphite negative electrode material, which is recorded as G;
[0037] (2) Add graphite powder and sodium nitrate in a mass ratio of 2:1 to concentrated sulfuric acid 25 times the mass of graphite powder, stir for 1 hour in an ice bath, slowly add potassium permanganate 1 times the mass of graphite powder and control the temperature below 20°C. After the addition of potassium permanganate is complete, stir and react for 4 hours in a 35°C water bath, then add deionized water 50 times the mass of graphite powder, heat to 80°C and continue to stir and react for 30 minutes, continue to add deionized water 50 times the mass of graphite powder, stir to room temperature, add an appropriate amount of hydrogen peroxide (30wt%) until there are no bubbles, wash with hydrochloric acid 3 times, and then wash with deionized water until neutral, freeze-dry, grind into powder, and obtain graphene oxide, recorded as GO;
[0038] (3) adding the recycled graphite negative electrode material to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a G dispersion with a solid content of 10 wt%; adding nano silicon dioxide (SiO) powder to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a SiO dispersion with a solid content of 1 wt%; adding graphene oxide to deionized water, and dispersing it uniformly by ultrasonic to obtain a GO dispersion with a solid content of 0.2 wt%; mixing the above G dispersion, SiO dispersion and GO dispersion in a mass ratio of G, SiO and GO of 10:0.75:0.35, and then dropping a N2H4·H2O solution (85 wt%) containing 2 wt% of G by mass into the mixed solution, performing a reduction reaction in a water bath at 85°C for 12 h, filtering with an organic filter membrane after cooling to room temperature, and vacuum drying to obtain a precursor composite material;
[0039] (4) The precursor composite material is placed in a muffle furnace for high-temperature carbonization reaction, with argon protective gas, the high-temperature carbonization temperature is 1100° C., the heating rate is 10° C. / min, and the time is 4 h to obtain a regenerated graphite negative electrode material, recorded as G-SiO-rGO.
[0040] Example 2
[0041] The present embodiment provides a method for recycling and modifying graphite negative electrode materials of spent batteries, which specifically includes:
[0042] (1) adding the negative electrode sheet of the lithium-ion battery after cycle failure to deionized water for ultrasonic dispersion, and after the graphite negative electrode material is completely separated from the current collector, taking out the current collector, collecting the obtained graphite negative electrode material, and then ultrasonically washing it with deionized water for 5 times, filtering it, vacuum drying it, and passing it through a 325-mesh sieve to obtain a recovered graphite negative electrode material, which is recorded as G;
[0043] (2) Add graphite powder and sodium nitrate in a mass ratio of 2:1 to concentrated sulfuric acid 25 times the mass of graphite powder, stir for 1 hour in an ice bath, slowly add potassium permanganate 1 times the mass of graphite powder and control the temperature below 20°C. After the addition of potassium permanganate is complete, stir and react for 4 hours in a 35°C water bath, then add deionized water 50 times the mass of graphite powder, heat to 80°C and continue to stir and react for 30 minutes, continue to add deionized water 50 times the mass of graphite powder, stir to room temperature, add an appropriate amount of hydrogen peroxide (30wt%) until there are no bubbles, wash with hydrochloric acid 3 times, and then wash with deionized water until neutral, freeze-dry, grind into powder, and obtain graphene oxide, recorded as GO;
[0044] (3) adding the recycled graphite negative electrode material to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a G dispersion with a solid content of 10 wt%; adding nano silicon dioxide (SiO) powder to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a SiO dispersion with a solid content of 1 wt%; adding graphene oxide to deionized water, and dispersing it uniformly by ultrasonic to obtain a GO dispersion with a solid content of 0.2 wt%; mixing the above G dispersion, SiO dispersion and GO dispersion in a mass ratio of G, SiO and GO of 10:0.5:0.2, and then dropping a N2H4·H2O solution (85 wt%) containing 2 wt% of G by mass into the mixed solution, performing a reduction reaction in a water bath at 85°C for 12 h, filtering with an organic filter membrane after cooling to room temperature, and vacuum drying to obtain a precursor composite material;
[0045] (4) The precursor composite material is placed in a muffle furnace for high-temperature carbonization reaction, with argon protective gas, the high-temperature carbonization temperature is 1100° C., the heating rate is 5° C. / min, and the time is 5 h to obtain a regenerated graphite negative electrode material, recorded as G-SiO-rGO.
[0046] Example 3
[0047] The present embodiment provides a method for recycling and modifying graphite negative electrode materials of spent batteries, which specifically includes:
[0048] (1) adding the negative electrode sheet of the lithium-ion battery after cycle failure to deionized water for ultrasonic dispersion, and after the graphite negative electrode material is completely separated from the current collector, taking out the current collector, collecting the obtained graphite negative electrode material, and then ultrasonically washing it with deionized water for 5 times, filtering it, vacuum drying it, and passing it through a 325-mesh sieve to obtain a recovered graphite negative electrode material, which is recorded as G;
[0049] (2) Add graphite powder and sodium nitrate in a mass ratio of 2:1 to concentrated sulfuric acid 25 times the mass of graphite powder, stir for 1 hour in an ice bath, slowly add potassium permanganate 1 times the mass of graphite powder and control the temperature below 20°C. After the addition of potassium permanganate is complete, stir and react for 4 hours in a 35°C water bath, then add deionized water 50 times the mass of graphite powder, heat to 80°C and continue to stir and react for 30 minutes, continue to add deionized water 50 times the mass of graphite powder, stir to room temperature, add an appropriate amount of hydrogen peroxide (30wt%) until there are no bubbles, wash with hydrochloric acid 3 times, and then wash with deionized water until neutral, freeze-dry, grind into powder, and obtain graphene oxide, recorded as GO;
[0050] (3) adding the recycled graphite negative electrode material to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a G dispersion with a solid content of 10 wt%; adding nano silicon dioxide (SiO) powder to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a SiO dispersion with a solid content of 1 wt%; adding graphene oxide to deionized water, and dispersing it uniformly by ultrasonic to obtain a GO dispersion with a solid content of 0.2 wt%; mixing the above G dispersion, SiO dispersion and GO dispersion in a mass ratio of G, SiO and GO of 10:1:0.5, and then adding sodium borohydride with a mass percentage of 2 wt% of G to the mixed solution, and performing reduction reaction in a water bath at 85°C for 12 h, cooling to room temperature, filtering with an organic filter membrane, and vacuum drying to obtain a precursor composite material;
[0051] (4) The precursor composite material is placed in a muffle furnace for high-temperature carbonization reaction, with argon protective gas, the high-temperature carbonization temperature is 1200° C., the heating rate is 10° C. / min, and the time is 3 h to obtain a regenerated graphite negative electrode material, recorded as G-SiO-rGO.
[0052] Example 4
[0053] The present embodiment provides a method for recycling and modifying graphite negative electrode materials of spent batteries, which specifically includes:
[0054] (1) adding the negative electrode sheet of the lithium-ion battery after cycle failure to deionized water for ultrasonic dispersion, and after the graphite negative electrode material is completely separated from the current collector, taking out the current collector, collecting the obtained graphite negative electrode material, and then ultrasonically washing it with deionized water for 5 times, filtering it, vacuum drying it, and passing it through a 325-mesh sieve to obtain a recovered graphite negative electrode material, which is recorded as G;
[0055] (2) Add graphite powder and sodium nitrate in a mass ratio of 2:1 to concentrated sulfuric acid 25 times the mass of graphite powder, stir for 1 hour in an ice bath, slowly add potassium permanganate 1 times the mass of graphite powder and control the temperature below 20°C. After the addition of potassium permanganate is complete, stir and react for 4 hours in a 35°C water bath, then add deionized water 50 times the mass of graphite powder, heat to 80°C and continue to stir and react for 30 minutes, continue to add deionized water 50 times the mass of graphite powder, stir to room temperature, add an appropriate amount of hydrogen peroxide (30wt%) until there are no bubbles, wash with hydrochloric acid 3 times, and then wash with deionized water until neutral, freeze-dry, grind into powder, and obtain graphene oxide, recorded as GO;
[0056] (3) adding nano-silicon dioxide (SiO) powder and 2,3-epoxypropyltrimethylammonium chloride (GTA) in a mass ratio of 20:1 to a mixed solution of ethanol / propylene glycol (v / v=9:1) containing 10 wt% sodium hydroxide, stirring and reacting in a water bath at 80° C. for 6 h, centrifuging, washing with ethanol three times, and drying to obtain silicon dioxide after quaternization pretreatment, recorded as GTA-SiO;
[0057] (4) adding the recycled graphite negative electrode material to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a G dispersion with a solid content of 10 wt%; adding the silicon oxide pretreated by quaternization to a mixed solvent consisting of deionized water and ethanol in a volume ratio of 5:3, and dispersing it uniformly by ultrasonic to obtain a GTA-SiO dispersion with a solid content of 1 wt%; adding graphene oxide to deionized water, and dispersing it uniformly by ultrasonic to obtain a GO dispersion with a solid content of 0.2 wt%; mixing the above-mentioned G dispersion, GTA-SiO dispersion and GO dispersion in a mass ratio of G, GTA-SiO and GO of 10:0.75:0.35, and then dropping a N2H4·H2O solution (85 wt%) containing 2 wt% of G by mass into the mixed solution, and performing a reduction reaction in a water bath at 85°C for 12 h, cooling to room temperature, filtering with an organic filter membrane, and vacuum drying to obtain a precursor composite material;
[0058] (5) The precursor composite material is placed in a muffle furnace for high-temperature carbonization reaction, with argon protective gas, the high-temperature carbonization temperature is 1100° C., the heating rate is 10° C. / min, and the time is 4 h to obtain a regenerated graphite negative electrode material, recorded as G-SiO-rGO.
[0059] The regenerated graphite negative electrode material and the recycled graphite negative electrode material obtained in the embodiment were stirred and mixed with conductive carbon black (SP) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 80:10:10, wherein PVDF was dissolved with N-methylpyrrolidone (NMP), and the obtained mixed slurry was evenly coated on a copper foil and dried in a vacuum drying oven at 110°C for 12h. The obtained electrode plate was used as the positive electrode of the simulated battery, the metal lithium plate was used as the negative electrode, the diaphragm was Celgard 2400 microporous polypropylene membrane, the electrolyte was 1 mol / L LiPF6 solution (solvent was EC / DMC, v / v=1:1, and assembled into a button battery CR2016 in a deoxygenated and dehydrated glove box filled with argon.
[0060] The button cell was placed on a LAND battery tester for electrochemical performance testing, with a charge and discharge voltage range of 0.001-2.0 V and a charge and discharge current of 0.1 C. The test results are listed in Table 1.
[0061] Table 1 Electrochemical test results of silicon-carbon negative electrode materials obtained in Examples and Comparative Examples
[0062]
[0063]
[0064] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for recycling and modifying graphite negative electrode materials of spent batteries, characterized in that: The steps include: S1. Dispersing the negative electrode sheets of the failed battery in water, collecting the graphite negative electrode material separated from the current collector, washing with deionized water for multiple times, and filtering to obtain the recovered graphite negative electrode material; S2, dispersing the recycled graphite negative electrode material, silicon dioxide and graphene oxide in a solvent respectively, mixing the obtained dispersions, and adding a reducing agent to carry out a reduction reaction to obtain a precursor composite material; S3. Carbonizing the precursor composite material at high temperature to obtain a regenerated graphite negative electrode material.
2. The method for recovering and modifying graphite negative electrode materials of failed batteries according to claim 1, characterized in that: In step S1, the failed battery is a lithium-ion battery whose capacity has dropped to less than 80% of the initial capacity.
3. The method for recovering and modifying graphite negative electrode materials of spent batteries according to claim 1 or 2, characterized in that: In step S2, the graphene oxide is prepared by using an improved Hummers method; and the silicon oxide is nano silicon oxide.
4. The method for recovering and modifying graphite negative electrode materials of spent batteries according to any one of claims 1 to 3, characterized in that: In step S2, the mass ratio of the recovered graphite negative electrode material, silicon dioxide and graphene oxide is 10:0.5-1:0.2-0.
5.
5. The method for recovering and modifying graphite negative electrode materials of spent batteries according to any one of claims 1 to 4, characterized in that: In step S2, the solvent is at least one of water, ethanol, propanol, ethylene glycol or nitrogen methyl pyrrolidone; Preferably, the solid content of the recycled graphite negative electrode material dispersed in the solvent is 5-15wt%, the solid content of the graphene oxide dispersed in the solvent is 0.1-1wt%, and the solid content of the silicon oxide dispersed in the solvent is 0.5-2wt%.
6. The method for recovering and modifying graphite negative electrode materials of spent batteries according to any one of claims 1 to 5, characterized in that: In step S2, the silicon dioxide is silicon dioxide pretreated by quaternization; Preferably, the quaternization pretreatment specifically comprises: performing a ring-opening coupling reaction on silicon oxide and epoxypropyltrimethylammonium chloride to obtain the product.
7. The method for recovering and modifying graphite negative electrode materials of spent batteries according to any one of claims 1 to 6, characterized in that: The reducing agent is at least one of hydrogen, hydrazine hydrate or sodium borohydride.
8. The method for recovering and modifying graphite negative electrode materials of spent batteries according to any one of claims 1 to 7, characterized in that: In step S3, the temperature of the high temperature carbonization reaction is 1000-1200°C and the time is 3-5h; Preferably, the heating rate of the high temperature carbonization reaction is 5-10°C / min.
9. A regenerated graphite negative electrode material obtained by the recovery and modification method according to any one of claims 1 to 8.
10. Use of the regenerated graphite negative electrode material according to claim 9 in a lithium ion battery.
Citation Information
Patent Citations
Preparation of high-energy graphene negative electrode material
CN107394185A
Silicon oxide-graphene composite material and preparation method therefor
CN107492645A
Graphene tightly coated SiO negative electrode material and preparation method thereof
CN109742363A
Method for recycling graphite negative electrode of lithium ion battery
CN113582171A
Preparation method for si / c negative electrode material having elastic shell layer-coated structure for lithium ion battery
WO2021258232A1
Cited By
Waste graphite repair material as well as preparation method and application thereof
CN120109341A
